2010
DOI: 10.1007/s11418-010-0408-7
|View full text |Cite
|
Sign up to set email alerts
|

A pterocarpan from the seeds of Bituminaria morisiana

Abstract: A new prenylated pterocarpan, named morisianine, was isolated together with the known secondary metabolites erybraedin C, psoralen and angelicin from the seeds of Bituminaria morisiana. The structures of the compounds were elucidated mainly by 1D and 2D NMR experiments as well as mass spectrometry. The new compound was subjected to cytotoxicity screening against a panel of human cancer cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…161 The majority of the new pterocarpans described in 2008-2011 are prenylated derivatives, with 44 examples documented . Remarkably, most of these originate from only two genera, Erythrina (152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163) and Lespedeza . Two exceptions are morisianine (150), a furanosubstituted pterocarpan isolated from seed extracts of Bituminaria morisiana, 162 and gangetial (151), which Varaprasad et al reported from Desmodium gangeticum roots.…”
Section: Rotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…161 The majority of the new pterocarpans described in 2008-2011 are prenylated derivatives, with 44 examples documented . Remarkably, most of these originate from only two genera, Erythrina (152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163) and Lespedeza . Two exceptions are morisianine (150), a furanosubstituted pterocarpan isolated from seed extracts of Bituminaria morisiana, 162 and gangetial (151), which Varaprasad et al reported from Desmodium gangeticum roots.…”
Section: Rotenoidsmentioning
confidence: 99%
“…Remarkably, most of these originate from only two genera, Erythrina (152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163) and Lespedeza . Two exceptions are morisianine (150), a furanosubstituted pterocarpan isolated from seed extracts of Bituminaria morisiana, 162 and gangetial (151), which Varaprasad et al reported from Desmodium gangeticum roots. 163 Previous work on the pterocarpans of Bituminaria revealed that 4-prenyl and 4,8-diprenyl derivatives are typical of this genus, which comprises only B. morisiana and the closely related B. bituminaria.…”
Section: Rotenoidsmentioning
confidence: 99%
“…Besides, the cytotoxic activity of this compound seems to be related to an induction of necrosis and not apoptosis [102]. A new prenylated pterocarpan, namely morisianine, obtained from B. morisiana seeds did not show any activity against Jurkat T, HL-60 (human leukemia), CaCo-2 (human epithelial colorectal adenocarcinoma) and MCF-7 (breast cancer) cell lines, up to the highest tested concentration [103].…”
Section: Anticancer Activitymentioning
confidence: 96%
“…Petroleum ether and ethyl acetate extracts from leaves of Bituminaria morisiana showed cytotoxic activity against KB-(HeLa) (KERATIN-forming tumor cell line HeLa) and immunocompetent Jurkat T-cells due to the pterocarpans, especially erybraedin C [102]. The comparison between the activities of all isolated pterocarpans suggested that the prenyl chain at C-8, as well as free hydroxyl groups at positions 3 and 9 in the pterocarpan nucleus, enhanced cytotoxicity [102,103]. Furthermore, the activity of erybraedin C was not influenced by the overexpression of the mitochondria protecting protein Bcl-2, suggesting that it acts against Jurkat T cells via a mechanism other than the mitochondrial apoptotic pathway.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Angelicin has been reported to exert antiproliferative and genotoxic effects, to induce hemolysis in erythrocytes, and inactivate prokaryotic and eukaryotic microorganisms, and viruses ( 9 11 ). In addition, angelicin has been reported to inhibit cell growth and/or induce cell death in several types of tumor ( 12 , 13 ), whereas it demonstrated reduced toxicity in healthy cells ( 14 ). However, the efficacy of angelicin against liver cancer, as well as its safety, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%